2009
DOI: 10.1186/1471-2180-9-187
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal activities of the cationic steroid CSA-13 and the cathelicidin peptide LL-37 against Helicobacter pylori in simulated gastric juice

Abstract: BackgroundThe worldwide appearance of drug-resistant strains of H. pylori motivates a search for new agents with therapeutic potential against this family of bacteria that colonizes the stomach, and is associated with adenocarcinoma development. This study was designed to assess in vitro the anti-H. pylori potential of cathelicidin LL-37 peptide, which is naturally present in gastric juice, its optimized synthetic analog WLBU2, and the non-peptide antibacterial agent ceragenin CSA-13.ResultsIn agreement with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 36 publications
4
39
0
2
Order By: Relevance
“…An in vitro study of CSA-13 susceptibility of seven strains of H. pylori (including clarithromycin and/or metronidazole-resistant strains) indicated MBCs of 0.275-8.9 µg/ml with CSA-13, while MBC values with LL-37 and WLBU2 (an engineered antimicrobial peptide) were 100-800 and 17.8-142 µg/ml, respectively [66].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…An in vitro study of CSA-13 susceptibility of seven strains of H. pylori (including clarithromycin and/or metronidazole-resistant strains) indicated MBCs of 0.275-8.9 µg/ml with CSA-13, while MBC values with LL-37 and WLBU2 (an engineered antimicrobial peptide) were 100-800 and 17.8-142 µg/ml, respectively [66].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Cathelicidins and defensins are examples of human antimicrobial peptides (AMPs) native to the innate immune system of many eukaryotes that have activity against H. pylori [150] . LL-37 is a cathelicidin with an anti-H. pylori effect [151] , and a recent study demonstrated that cathelicidin limited H. pylori colonization and related gastritis in mouse models [152] . Defensin peptides have also been indicated to impede H. pylori [153] .…”
Section: Eradication: Hope Is Coming?mentioning
confidence: 99%
“…Dodatnio naładowana cząsteczka CsA-13, naruszając integralność ściany komórkowej mikroorganizmu, wykazuje działanie bakteriobójcze wobec patogenów G(+) i G(-), w tym szczepów bakterii H. pylori opornych na MTZ i/lub CL. Wyniki badań in vitro pokazują, że aktywność przeciwbakteryjna cząsteczki CsA-13 nie zmienia się po preinkubacji w roztworach naśladujących sok żołądko-wy o pH 1,5 z dodatkiem pepsyny lub mucyny [46].…”
Section: Nowe Substancjeunclassified